Textile printing ink set
Patent Information
- Application Number
- JP2020198447
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-11-30
AI Technical Summary
【0008】 本発明によれば、水系白インクを用いたインクジェット捺染であっても、良好な風合い、低タック性、白色度を維持しつつ、摩擦堅牢性に優れた印捺物を得ることができる捺染用インクセットを提供することができる。
Smart Images

Figure 0007638685000001 
Figure 0007638685000002 
Figure 0007638685000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a textile printing ink set. [Background technology]
[0002] Textile printing is a coloring method for applying patterns to fabrics such as cloth and textile products. Screen printing and roller printing are widely used, but in recent years, inkjet printing methods that utilize inkjet recording methods have been studied. The inkjet printing method is a method of printing by ejecting ink droplets and depositing them on a fabric, and has the advantage that the mechanism is relatively simple and it can form high-definition, high-quality images. In addition, unlike conventional methods, there is no need to create a plate, so images with excellent gradation can be quickly formed, making it possible to handle small-lot, high-mix production, and it is also environmentally friendly, as only the small amount of ink required for the image is used, resulting in less waste liquid.
[0003] On the other hand, there are two types of ink for textile printing: dye ink and pigment ink. Pigment ink is more convenient than dye ink because it has high light resistance and does not require post-processing. Here, white ink is used to express white on fabric or as a base to improve the color development of color inks when coloring, but in this case, it is necessary to sufficiently conceal the color of the fabric with the white ink. When printing with white pigment ink, a fabric coated with a pretreatment agent is usually used to suppress the penetration of the ink into the fabric. By applying a pretreatment agent, the ink is aggregated on the surface of the fabric, suppressing the penetration of the ink into the fabric and improving the hiding power. However, there is a problem that the adhesion between the ink coating and the fabric is weakened, and sufficient friction fastness cannot be obtained.
[0004] As an inkjet recording method using a white ink that combines dispersion stability and hiding power, Patent Document 1 discloses a recording method in which a surface treatment liquid composition and an ink are adhered to a recording medium, in which the liquid composition contains nonionic resin particles and a polyvalent metal salt, and the ink contains a volatile solvent, a pigment, and resin particles, and the pigment is an ink that is a spherical inorganic hollow particle. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-178322 A Summary of the Invention [Problem to be solved by the invention]
[0006] Inkjet printing using white pigment ink has the problem of improving the abrasion fastness as mentioned above, but in addition, the whiteness tends to decrease because the amount of colorant attached to the fabric is small compared to screen printing, etc. In addition, the obtained printed matter is required to have a good feel and low tackiness (lack of stickiness). An object of the present invention is to provide a textile printing ink set that can provide printed textiles with excellent friction fastness while maintaining good texture, low tackiness, and whiteness, even in ink-jet textile printing using a water-based white ink. [Means for solving the problem]
[0007] The present inventors have found that the above problems can be solved by combining a printing pretreatment agent containing an ethylene-vinyl acetate resin with a water-based white ink containing titanium oxide and a specific water-soluble organic solvent. That is, the present invention provides a printing ink set including a water-based white ink and a printing pretreatment agent, the printing pretreatment agent including an ethylene-vinyl acetate resin and water, The present invention provides a textile printing ink set, in which the water-based white ink contains titanium oxide and one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, 2-pyrrolidone, and diethylene glycol monoethyl ether. Effect of the Invention
[0008] According to the present invention, it is possible to provide a textile printing ink set which is capable of producing printed textiles having excellent friction fastness while maintaining good texture, low tackiness, and whiteness, even in inkjet textile printing using a water-based white ink. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Textile printing ink set] The textile printing ink set of the present invention is a textile printing ink set including a water-based white ink and a textile printing pretreatment agent, the textile printing pretreatment agent including an ethylene-vinyl acetate resin and water, The water-based white ink contains titanium oxide and one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, 2-pyrrolidone, and diethylene glycol monoethyl ether. In this specification, the term "aqueous system" means that water accounts for the largest proportion of the medium. Further, the term "printed textile" refers to an item on which an image or the like is formed by printing ink on the surface of a fabric, which is a printing medium. The textile printing ink set of the present invention is particularly useful for ink-jet textile printing.
[0010] According to the textile printing ink set of the present invention, even in ink-jet textile printing using a water-based white ink, it is possible to obtain printed textiles that have excellent texture, low tackiness, and whiteness while maintaining excellent fastness to friction. The reason for this is unclear, but is thought to be as follows. The textile printing pretreatment agent used in the ink set of the present invention contains an ethylene-vinyl acetate resin, which has a relatively large number of acetoxy groups at appropriate intervals within the molecule and has flexibility and low elastic modulus, and is therefore considered to have excellent adhesion to fabrics and not to deteriorate the texture. In addition, the ethylene-vinyl acetate resin is considered to impart lubricity to the surface of the printed textile, contributing to the improvement of the friction fastness. On the other hand, the water-based white ink according to the present invention contains one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, 2-pyrrolidone, and diethylene glycol monoethyl ether. It is believed that these water-soluble organic solvents easily wet the ethylene-vinyl acetate resin, thereby improving the interfacial adhesion and the abrasion fastness. In addition, since the content of the water-soluble organic solvent in the water-based white ink can be made relatively small, the water-based white ink does not penetrate the fabric and remains on the surface of the fabric, which is thought to further improve hiding power.
[0011] <Pretreatment agent for textile printing> The pretreatment agent for textile printing (hereinafter, also simply referred to as "pretreatment agent") used in the present invention is used in pretreatment for textile printing in order to improve the poor ink absorbency and fixability of fabrics and to obtain printed textiles that have excellent friction fastness while maintaining good texture, low tackiness, and whiteness in ink-jet textile printing, etc. The pretreatment agent contains at least an ethylene-vinyl acetate resin and water.
[0012] [Ethylene-vinyl acetate resin] Ethylene-vinyl acetate resin is a resin obtained by copolymerizing ethylene monomer and vinyl acetate monomer, etc. Ethylene-vinyl acetate resin can be obtained, for example, by copolymerizing ethylene monomer and vinyl acetate monomer by emulsion polymerization method using polyvinyl alcohol or the like as a protective colloid and a cellulose derivative such as hydroxyethyl cellulose or a surfactant as an emulsifying dispersant.
[0013] The ethylene-vinyl acetate resin used in the present invention may contain structural units derived from other monomers other than structural units derived from ethylene monomers and structural units derived from vinyl acetate monomers, to the extent that the effects of the present invention are not impaired. Examples of such other monomers include (meth)acrylic acid, vinyl chloride, vinyl propionate, vinyl butanoate, vinyl hexanoate, etc. In other words, the ethylene-vinyl acetate resin according to the present invention also includes resins containing other monomers as structural units in addition to ethylene monomers and vinyl acetate monomers. In the ethylene-vinyl acetate resin according to the present invention, from the viewpoint of obtaining a printed material having excellent friction fastness while maintaining a good texture, low tackiness, and whiteness, the content of structural units derived from vinyl acetate is preferably 10% by mass or more and 45% by mass or less, more preferably 15% by mass or more and 40% by mass or less, and even more preferably 20% by mass or more and 35% by mass or less.
[0014] From the viewpoint of obtaining printed matter having excellent resistance to rubbing, etc., the glass transition temperature (Tg) of the ethylene-vinyl acetate resin is preferably −35° C. or higher, more preferably −30° C. or higher, even more preferably −25° C. or higher, still more preferably −20° C. or higher, and is preferably 10° C. or lower, more preferably 8° C. or lower, even more preferably 5° C. or lower, and still more preferably 2° C. or lower. The glass transition temperature of ethylene-vinyl acetate resin can be adjusted by the content of the monomers constituting the resin. In general, the glass transition temperature of ethylene-vinyl acetate resin decreases as the content of ethylene monomer increases, and the glass transition temperature of ethylene-vinyl acetate resin increases as the content of vinyl acetate monomer increases. The glass transition temperature can be calculated from the mass ratio of the monomers in each polymer portion according to the following Fox equation. 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+···+(W m / Tg m ) W1+W2+...W m =1 In the Fox formula, Tg is the glass transition temperature of the polymer, and Tg1, Tg2, . . . , Tg mis the glass transition temperature of each polymer monomer. The unit of temperature is K. Also, W1, W2, ..., W m represents the mass ratio of each polymerizable monomer. As the glass transition temperature of each polymerizable monomer in the Fox formula, for example, the value described in Polymer Handbook Third Edition (Wiley-Interscience 1989) can be used. The glass transition temperature of the styrene-acrylic resin used in the comparative examples can also be calculated by the Fox equation.
[0015] The ethylene-vinyl acetate resin is preferably in the form of fine particles, and more preferably used in the form of an emulsion. When the ethylene-vinyl acetate resin is in the form of fine particles, from the viewpoints of maintaining the storage stability of the pretreatment agent, and good texture, low tackiness, and whiteness, the average particle size is preferably 1.2 μm or less, more preferably 1.0 μm or less, even more preferably 0.9 μm or less, and is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.4 μm or more, and still more preferably 0.5 μm or more. The average particle size of the ethylene-vinyl acetate resin can be measured using a laser particle analysis system, etc. The average particle size of the ethylene-vinyl acetate resin can be adjusted by the concentration of the emulsifier during emulsion polymerization, the concentration of the polymerization initiator, etc.
[0016] The pretreatment agent used in the present invention may contain a known resin other than ethylene-vinyl acetate resin as a binder, as long as the effect of the present invention is not impaired. Examples of such known resins include polyvinyl alcohol and various modified polyvinyl alcohols. Furthermore, the pretreatment agent may contain various known additives, as necessary, such as a dispersant, a fixing agent, a cationizing agent, a thickener, a flow improver, an antifoaming agent, a foaming agent, a penetrating agent, an ultraviolet absorber, an antioxidant, an antiseptic, and an antifungal agent.
[0017] Commercially available ethylene-vinyl acetate resins can also be used, examples of which include Sumikaflex 201HQ, 305HQ, 355HQ, 400HQ, 401HQ, 408HQ, 410HQ, 450HQ, 455HQ, 456HQ, 460HQ, 465HQ, 467HQ, 7400HQ, 470HQ, 510HQ, and 755, both of which are manufactured by Sumika Chemtex Corporation, Chemipearl series, which are manufactured by Mitsui Chemicals, Inc., and Panflex series, which are manufactured by Kuraray Co., Ltd. Commercially available examples of ethylene-vinyl acetate-(meth)acrylic acid based resins include Sumikaflex 900HL, 950HQ, 951HQ, etc., manufactured by Sumika Chemtex Corporation, and commercially available examples of ethylene-vinyl acetate-vinyl chloride based resins include Sumikaflex 850HQ, etc., manufactured by Sumika Chemtex Corporation.
[0018] From the viewpoint of obtaining a printed material having excellent friction fastness while maintaining good texture, low tackiness, and whiteness, the content of the ethylene-vinyl acetate resin in the pretreatment agent is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, even more preferably 1.0% by mass or more, still more preferably 1.2% by mass or more, and is preferably 10% by mass or less, more preferably 9% by mass or less, even more preferably 8% by mass or less, and still more preferably 6% by mass or less.
[0019] [Polyvalent metal salt] The pretreatment agent used in the present invention preferably further contains a polyvalent metal salt from the viewpoint of increasing the cation concentration and improving the resistance to rubbing, etc. It is believed that the polyvalent metal salt acts as an ink flocculant that flocculates titanium oxide in the ink, and also causes the fixing resin to precipitate, thereby enabling the formation of a strong ink coating on the fabric. Examples of polyvalent metal salts include salts of titanium compounds, chromium compounds, copper compounds, cobalt compounds, strontium compounds, barium compounds, iron compounds, aluminum compounds, calcium compounds, magnesium compounds, etc. Among these, from the viewpoint of effectively agglomerating titanium oxide and improving friction fastness, etc., one or more selected from aluminum salts, calcium salts, and magnesium salts are preferred, alkaline earth metal salts such as calcium salts and magnesium salts are more preferred, and calcium salts are even more preferred. When the polyvalent metal salt is a calcium salt, the stability of the pretreatment agent is increased, and even when the fabric after pretreatment is hot-pressed, salts are less likely to precipitate on the fabric surface. Specific examples of calcium salts include calcium carbonate, such as heavy calcium carbonate and light calcium carbonate, calcium nitrate, calcium chloride, calcium sulfate, calcium silicate, and the like. From the viewpoints of ensuring water solubility and reducing traces of the pretreatment agent, one or more selected from calcium nitrate and calcium chloride are preferred, and calcium chloride is more preferred. The polyvalent metal salts can be used alone or in combination of two or more kinds.
[0020] From the viewpoint of improving the resistance to rubbing and the like, the blending amount (content) of the polyvalent metal salt in the pretreatment agent is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, and is preferably 15% by mass or less, more preferably 10% by mass or less, even more preferably 6% by mass or less. Furthermore, from the viewpoint of improving whiteness, friction fastness, and the like, the cation concentration (metal ion content) in the pretreatment agent is preferably 0.2 mmol / g or more, more preferably 0.3 mmol / g or more, and preferably 8 mmol / g or less, more preferably 7 mmol / g or less, and even more preferably 6 mmol / g or less. The cation concentration in the pretreatment agent is calculated by the following formula. Cation concentration in pretreatment agent (mmol / g) = number of moles of cationic groups in 1 g of pretreatment agent × valence From the viewpoint of achieving both good texture and whiteness, the amount (content) of water in the pretreatment agent is preferably 85% by mass or more, more preferably 90% by mass or more, and is preferably 98% by mass or less, more preferably 96% by mass or less.
[0021] <Water-based white ink> The water-based white ink used in the present invention contains titanium oxide and one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, 2-pyrrolidone, and diethylene glycol monoethyl ether.
[0022] [Titanium oxide] As the titanium oxide, rutile type titanium dioxide and anatase type titanium dioxide can be used, but from the viewpoints of stability and availability, rutile type titanium dioxide is preferred. From the viewpoint of improving the dispersion stability, the titanium oxide is preferably surface-treated. The surface treatment of the titanium oxide is not particularly limited, and may be surface-treated with either an organic substance or an inorganic substance. From the viewpoint of suppressing the photocatalytic activity, the titanium oxide surface-treated with an inorganic substance is preferable, and the titanium dioxide surface-treated with silica and alumina is more preferable. The average primary particle size of titanium oxide is, from the viewpoint of whiteness, preferably 100 nm or more, more preferably 150 nm or more, and even more preferably 200 nm or more, and, from the viewpoint of redispersibility, preferably 500 nm or less, more preferably 400 nm or less, even more preferably 350 nm or less, and even more preferably 300 nm or less. The average primary particle size of titanium oxide is measured by the method described in the Examples. Examples of commercially available rutile titanium dioxide products include the Typec R, CR, and PF series manufactured by Ishihara Sangyo Kaisha, Ltd., the R series manufactured by Sakai Chemical Industry Co., Ltd., the JR and MT series manufactured by Teika Corporation, the KURONOS KR series manufactured by Titan Kogyo Co., Ltd., and the TR series manufactured by Fuji Titan Kogyo Co., Ltd.
[0023] Titanium oxide is preferably held in a dispersed state in the ink by a dispersant, and a polymer dispersant is preferred as the dispersant for dispersing titanium oxide. The titanium oxide and polymer dispersant in the water-based white ink are preferably present in the form of polymer particles containing titanium oxide (hereinafter also referred to as "pigment-containing polymer particles"). The pigment-containing polymer particles refer to any one of particles in which the polymer dispersant encapsulates titanium oxide, particles in which part of the titanium oxide is exposed on the surface of particles made of a polymer dispersant and titanium oxide, particles in which the polymer dispersant is adsorbed to part of the titanium oxide, or mixtures thereof. Among these, the form in which the titanium oxide is encapsulated in the polymer dispersant is more preferred.
[0024] [Polymer particles containing titanium oxide] The polymer (hereinafter also referred to as "polymer a") constituting the polymer particles containing titanium oxide (pigment-containing polymer particles) is not particularly limited as long as it has at least the ability to disperse titanium oxide, but a water-insoluble polymer is preferred. In the present invention, the term "water-insoluble" for polymer a means that when the polymer is dried at 105° C. for 2 hours and reaches a constant weight, and then dissolved in 100 g of water at 25° C., the amount of dissolution is 10 g or less. When polymer a is an anionic polymer, the amount of dissolution is the amount of dissolution when the anionic groups of the polymer are 100% neutralized with sodium hydroxide.
[0025] The polymer a preferably has an ionic group from the viewpoint of improving the dispersion stability of titanium oxide, etc. The ionic group is preferably an acid group. The ionic group contained in the molecule of the polymer a is preferably one that is introduced into the polymer skeleton by the ionic monomer (a-1), i.e., the polymer a preferably contains a structural unit derived from the ionic monomer (a-1). Examples of the polymer a include vinyl resins, polyester resins, and polyurethane resins, with vinyl resins being preferred. The vinyl resin may contain, in addition to the structural units derived from the component (a-1), structural units derived from a hydrophobic monomer (a-2) and structural units derived from a nonionic monomer (a-3).
[0026] [Ionic Monomer (a-1)] The ionic monomer (a-1) is preferably an anionic monomer, such as a carboxylic acid monomer, a sulfonic acid monomer, etc. Of these, the carboxylic acid monomer is more preferred. Examples of the carboxylic acid monomer include (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, and fumaric acid, and preferably (meth)acrylic acid. "(Meth)acrylic acid" means at least one selected from acrylic acid and methacrylic acid.
[0027] [Hydrophobic monomer (a-2)] The term "hydrophobic" in the hydrophobic monomer (a-2) means that when the monomer is dissolved in 100 g of ion-exchanged water at 25° C. until saturation, the amount of the monomer that dissolves is less than 10 g. Examples of the hydrophobic monomer (a-2) include alkyl (meth)acrylates, aromatic group-containing monomers, and macromonomers having a polymerizable functional group at one end. Specific examples of the (a-2) component include those described in paragraphs
[0020] to
[0022] of JP 2018-83938 A. Among these, one or more selected from alkyl (meth)acrylates having an alkyl group having 1 to 22 carbon atoms, styrene, α-methylstyrene, and benzyl (meth)acrylate are preferred.
[0028] [Nonionic monomer (a-3)] The nonionic monomer (a-3) is a monomer that has a high affinity for water or a water-soluble organic solvent, and is, for example, a monomer that contains a hydroxyl group or a polyalkylene glycol chain. Specific examples of the (a-3) component include those described in paragraph
[0018] of JP 2018-83938 A. Among these, one or more selected from methoxypolyethylene glycol (n = 1 to 30) (meth)acrylate and polypropylene glycol (n = 2 to 30) (meth)acrylate are preferred. Specific examples of commercially available nonionic monomers (a-3) include the NK Ester M series manufactured by Shin-Nakamura Chemical Co., Ltd. and the Blenmer series manufactured by NOF Corporation.
[0029] (Content of each structural unit in vinyl resin) From the viewpoint of improving the dispersion stability of titanium oxide, the contents of the structural units derived from the components (a-1) to (a-3) in the vinyl resin are as follows. The content of the (a-1) component is preferably 40 mass % or more, more preferably 50 mass % or more, even more preferably 60 mass % or more, still more preferably 70 mass % or more, and preferably 100 mass % or less. When the component (a-2) is contained, the content thereof is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less. When the component (a-3) is contained, the content thereof is preferably 1% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less.
[0030] (Production of vinyl resins) The vinyl resin is produced by copolymerizing the raw material monomer (a) by a known polymerization method such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. Among these polymerization methods, the solution polymerization method is preferred. The solvent used in the solution polymerization method is not particularly limited, but a polar organic solvent is preferred. Examples of the polar organic solvent include aliphatic alcohols having 1 to 3 carbon atoms, ketones having 3 to 5 carbon atoms, ethers, esters such as ethyl acetate, etc., and a mixed solvent of one or more of these with water is also preferred. In the polymerization, a known polymerization initiator or a polymerization chain transfer agent can be used.
[0031] Preferred polymerization conditions vary depending on the types of polymerization initiator, monomer, solvent, etc. used, but usually the polymerization temperature is preferably 30° C. or higher, more preferably 50° C. or higher, and preferably 95° C. or lower, more preferably 80° C. or lower. The polymerization atmosphere is preferably a nitrogen gas atmosphere, an inert gas atmosphere such as argon, etc. From the viewpoint of improving the adsorptivity to titanium oxide and the dispersion stability, the weight average molecular weight of the vinyl resin is preferably 2000 or more, more preferably 3000 or more, and even more preferably 4000 or more, and is preferably 50,000 or less, more preferably 20,000 or less. The weight average molecular weight is measured by the method described in the Examples.
[0032] [Preparation of pigment-containing polymer particles] The pigment-containing polymer particles can be efficiently produced as a pigment aqueous dispersion by a method having the following step I. Step I: A step of dispersing a pigment mixture containing titanium oxide, polymer a, and water to obtain an aqueous dispersion of pigment-containing polymer particles (hereinafter also referred to as "aqueous pigment dispersion (i)"). In the present invention, a crosslinking agent may be further added to the resulting pigment water dispersion (i) to perform a crosslinking treatment.
[0033] The pigment mixture in step I is preferably obtained by a method in which titanium oxide, water, and, if necessary, a neutralizer, a surfactant, and the like are added to polymer a, mixed, and then dispersed. When polymer a has acid groups, it is preferable that at least a portion of the acid groups is neutralized with a neutralizing agent, which is believed to increase the charge repulsion force exhibited after neutralization and improve the dispersion stability of titanium oxide in the water-based white ink. In the case of neutralization, it is preferable to neutralize so that the pH is 7 or more and 11 or less. Examples of the neutralizing agent include bases such as sodium hydroxide, potassium hydroxide, ammonia, and various amines, with sodium hydroxide and ammonia being preferred. Moreover, the polymer a may be neutralized in advance. From the viewpoint of improving dispersion stability, the amount of the neutralizing agent used is preferably 10 mol % or more, more preferably 20 mol % or more, even more preferably 30 mol % or more, and is preferably 150 mol % or less, more preferably 120 mol % or less, even more preferably 100 mol % or less. Here, the equivalent amount of the neutralizing agent used can be calculated by the following formula, where polymer a before neutralization is "polymer a'". Equivalent amount of neutralizing agent used (mol%)=[{weight of neutralizing agent added (g) / equivalent amount of neutralizing agent} / [{acid value of polymer a' (mg KOH / g) × weight of polymer (B) (g)} / (56 × 1,000)]] × 100
[0034] In the dispersion treatment in step I, the titanium oxide particles can be atomized to the desired particle size simply by main dispersion using shear stress, but from the viewpoint of obtaining a uniform aqueous pigment dispersion, the pigment mixture can be pre-dispersed and then further main dispersed. As a dispersing machine used for preliminary dispersion, a commonly used mixing and stirring device such as an anchor blade or a dispersing blade can be used. Examples of means for applying the shear stress used in the present dispersion include kneading machines such as roll mills and kneaders, high-pressure homogenizers such as microfluidizers, and media-type dispersers such as paint shakers and bead mills. Among these, from the viewpoint of reducing the particle size of titanium oxide, it is preferable to use high-pressure homogenizers and bead mills.
[0035] When an organic solvent is used in step I, it is preferable to remove the organic solvent after step I. There is no limitation on the organic solvent used, but ketones, ethers, esters, aliphatic alcohols having 1 to 3 carbon atoms, etc. are preferable, and from the viewpoint of improving the wettability to titanium oxide and the solubility of polymer a, ketones having 4 to 8 carbon atoms are more preferable. When a vinyl resin is synthesized as polymer a by solution polymerization, the solvent used in the polymerization may be used as it is. The organic solvent can be removed by a known method. In addition, for the purpose of removing coarse particles and the like, it is preferable to further centrifuge the aqueous dispersion from which the organic solvent has been removed, and then filter the liquid layer portion with a filter or the like to obtain a pigment aqueous dispersion (i).
[0036] From the viewpoint of improving the dispersion stability of the pigment water dispersion, the non-volatile component concentration (solid content concentration) of the obtained pigment water dispersion (i) is preferably 20 mass % or more, more preferably 30 mass % or more, even more preferably 40 mass % or more, and is preferably 65 mass % or less, more preferably 60 mass % or less, even more preferably 55 mass % or less. The solids concentration is measured by the method described in the Examples. From the viewpoint of dispersion stability, the content of titanium oxide in the pigment water dispersion (I) is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and preferably 65% by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less. From the viewpoint of improving dispersion stability, the average particle size of the pigment-containing polymer particles is preferably 50 nm or more, more preferably 100 nm or more, even more preferably 150 nm or more, and is preferably 500 nm or less, more preferably 450 nm or less, even more preferably 350 nm or less. The average particle size of the pigment-containing polymer particles is measured by the method described in the Examples.
[0037] [Fixing resin] The water-based white ink according to the present invention preferably contains a fixing resin from the viewpoint of improving the abrasion fastness, etc. The fixing resin does not contain a pigment and is polymer particles constituted solely by a polymer. Suitable examples of the fixing resin include urethane resin, polyester resin, acrylic resin, etc., with urethane resin being preferred among these. Examples of the urethane resin include polycarbonate-based urethane resins having a carbonate bond, polyester-based urethane resins having an ester bond, and polyether-based urethane resins having an ether bond, among which polycarbonate-based urethane resins are preferred from the viewpoint of improving the friction fastness of the resulting printed matter, etc. The polycarbonate-based urethane resin also preferably contains a crosslinkable group such as an isocyanate group or a silanol group. The fixing resin is preferably used in an emulsion state. The fixing resin may be synthesized or may be a commercially available product. Commercially available examples of polycarbonate-based urethane resins include Superflex 150, 170, 420, 460, 470, 610, 700, and 800 manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and Permarin UA and U-coat UX manufactured by Sanyo Chemical Industries, Ltd.
[0038] [Water-soluble organic solvent] The water-based white ink according to the present invention contains one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, 2-pyrrolidone, and diethylene glycol monoethyl ether, from the viewpoint of obtaining printed matter having excellent friction fastness while maintaining good texture, low tackiness, and whiteness. The water-soluble organic solvent is preferably at least one selected from tripropylene glycol monomethyl ether and dipropylene glycol monobutyl ether. The boiling point of the water-soluble organic solvent is 200° C. or higher and 255° C. or lower.
[0039] The water-based white ink according to the present invention can contain, as the water-soluble organic solvent, glycol ethers such as alkylene glycol monoalkyl ethers and alkylene glycol dialkyl ethers other than the above-mentioned water-soluble organic solvents, alkanediols such as propylene glycol, dipropylene glycol, diethylene glycol, 1,2-hexanediol, and polyhydric alcohols such as glycerin, within a range that does not impair the effects of the present invention. Among these, one or more selected from glycerin and propylene glycol are preferred, and it is more preferred to contain both glycerin and propylene glycol.
[0040] [Surfactant] The water-based white ink according to the present invention preferably contains a surfactant from the viewpoint of improving resistance to friction, etc. The surfactant is preferably a nonionic surfactant, more preferably one or more selected from an acetylene glycol surfactant and a silicone surfactant, and even more preferably an acetylene glycol surfactant and a silicone surfactant are used in combination.
[0041] (Acetylene glycol surfactant) Examples of acetylene glycol surfactants include acetylene diols such as 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,6-dimethyl-4-octyne-3,6-diol, 3,5-dimethyl-1-hexyne-3-ol, and 2,4-dimethyl-5-hexyne-3-ol, as well as ethylene oxide adducts thereof. The sum (n) of the average number of moles of ethyleneoxy groups (EO) added in the ethylene oxide adduct is preferably 1 or more, more preferably 1.5 or more, and is preferably 20 or less, more preferably 10 or less. Commercially available examples of acetylene glycol surfactants include the "Surfynol" series and "Olfine" series manufactured by Nissin Chemical Industry Co., Ltd., and the "Acetylenol" series manufactured by Kawaken Fine Chemicals Co., Ltd.
[0042] (Silicone surfactant) Examples of silicone surfactants include dimethylpolysiloxane, polyether-modified silicone, amino-modified silicone, and carboxy-modified silicone, with polyether-modified silicone being preferred from the same viewpoint as above. Specific examples of polyether-modified silicone surfactants include the KF series manufactured by Shin-Etsu Chemical Co., Ltd., the Silface SAG series manufactured by Nissin Chemical Industry Co., Ltd., and the BYK series manufactured by BYK Japan KK.
[0043] The water-based white ink according to the present invention can be efficiently produced by mixing the pigment water dispersion (i), a water dispersion of a fixing resin, a water-soluble organic solvent, and, if necessary, a surfactant, etc. There are no particular limitations on the method of mixing them. Furthermore, various additives commonly used in water-based inks, such as humectants, wetting agents, viscosity adjusters, defoamers, preservatives, antifungal agents, and rust inhibitors, may also be added.
[0044] (Content of each component in water-based white ink) The content of each component in the water-based white ink according to the present invention is as follows, from the viewpoint of improving whiteness, friction fastness, and the like. (Titanium oxide content) The content of titanium oxide in the white ink is preferably 5% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and is preferably 20% by mass or less, more preferably 18% by mass or less, even more preferably 15% by mass or less. (Content of pigment-containing polymer particles) The content of the pigment-containing polymer particles in the white ink is preferably 5% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and is preferably 25% by mass or less, more preferably 23% by mass or less, even more preferably 20% by mass or less.
[0045] (Fixing resin content) When the white ink contains a fixing resin, the content thereof is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 5% by mass or more, and preferably 20% by mass or less, more preferably 18% by mass or less, even more preferably 15% by mass or less. The mass ratio of the fixing resin to the pigment-containing polymer particles [fixing resin / pigment-containing polymer particles] is preferably 0.2 or more, more preferably 0.4 or more, even more preferably 0.5 or more, and is preferably 2 or less, more preferably 1.5 or less, even more preferably 1.2 or less.
[0046] The mass ratio of polymer to titanium oxide in the white ink [polymer / titanium oxide] is preferably 0.2 or more, more preferably 0.4 or more, even more preferably 0.5 or more, and is preferably 2 or less, more preferably 1.5 or less, even more preferably 1.2 or less. In addition, since the water-based white ink according to the present invention contains pigment-containing polymer particles and a fixing resin, the amount of polymer in the above mass ratio [polymer / titanium oxide] is the total amount of polymer a and the fixing resin.
[0047] (Water-soluble organic solvent content) The total content of one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, 2-pyrrolidone, and diethylene glycol monoethyl ether in the white ink is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 1.5% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less.
[0048] (Surfactant content) The content of the surfactant in the white ink is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and is preferably 5% by mass or less, more preferably 4% by mass or less, even more preferably 3% by mass or less. The content of the acetylene glycol surfactant in the white ink is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, even more preferably 0.05% by mass or more, and preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. The content of the silicone surfactant in the white ink is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, even more preferably 0.05% by mass or more, and preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. (Water content) The water content in the white ink is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less.
[0049] (Physical properties of water-based white ink) From the viewpoint of improving dispersion stability, the viscosity of the white ink at 25°C is preferably 2 mPa·s or more, and more preferably 3 mPa·s or more, and is preferably 20 mPa·s or less, and more preferably 15 mPa·s or less. The pH of the white ink at 25°C is preferably 5.5 or more, more preferably 6.0 or more, and even more preferably 6.5 or more, from the viewpoint of improving dispersion stability, and is preferably 11.0 or less, more preferably 10.5 or less, and even more preferably 10.0 or less, from the viewpoints of component resistance and skin irritation.
[0050] [Printing method] A textile printing method using the textile printing ink set of the present invention preferably includes the following steps 1 and 2. Step 1: A step of applying a printing pretreatment agent containing ethylene-vinyl acetate resin and water to the fabric. Step 2: A step of applying a water-based white ink to the fabric obtained in step 1. It is preferable to provide a step of drying the fabric between steps 1 and 2. The printing method is preferably an ink-jet printing method. According to the textile printing method of the present invention, even in the case of ink-jet textile printing, it is possible to obtain a printed textile having excellent friction fastness while maintaining good texture, low tackiness, and whiteness.
[0051] (Process 1) There is no particular limitation on the method for attaching the pretreatment agent to the printing area of the fabric in step 1. Examples of known methods include a method of immersing the fabric in the pretreatment agent, a method of applying the agent to the entire surface or the printing area of the fabric using various coaters (including inkjet printers), and a spraying method. The fabric that is the printing medium may be any of those that have been used conventionally, such as fabrics made of natural fibers such as cotton, silk, and hemp, and synthetic fibers such as rayon, acetate, nylon, and polyester, and blended fabrics made of two or more of these fibers. It is preferable that the fabric before being treated with the pretreatment agent is not colored or dyed with a pigment or the like. The amount of the pretreatment agent applied to the fabric is preferably 1 g / m2 in terms of the whiteness after drying. 2 More preferably, 3 g / m 2 From the viewpoint of not impairing the texture, it is preferably 30 g / m 2 Less than 20 g / m 2 The following is the result.
[0052] It is preferable to have a step of drying the fabric to which the pretreatment agent is attached, if necessary, after the end of step 1 and before the start of step 2. There are no particular limitations on the method for drying the fabric, but from the viewpoint of the fixation of the pretreatment agent, heat treatment can be performed at preferably 50° C. or higher, more preferably 70° C. or higher, for one minute to one hour, and from the viewpoint of preventing deterioration of the fabric and the pretreatment agent, at preferably 180° C. or lower, more preferably 170° C. or lower.
[0053] (Process 2) In step 2, the method for applying the water-based white ink to the fabric obtained in step 1 for printing is not particularly limited, but a method for printing using an inkjet printing device is preferred. For example, a drop-on-demand type inkjet printing device can be used. Examples of this inkjet printing device include a piezoelectric type device using a piezoelectric element arranged on the head, and a thermal type device using thermal energy from a heater or the like of a heat generating resistor element arranged on the head, with the piezoelectric type inkjet printing device being more preferred.
[0054] (Inkjet printing device) In a piezoelectric inkjet printing device, a large number of nozzles are connected to pressure chambers, and ink droplets are ejected from the nozzles by vibrating the walls of the pressure chambers with a piezoelectric element. The printing conditions for the inkjet printing device are as follows: The voltage applied to the print head is preferably 5V or more, more preferably 10V or more, and is preferably 40V or less, more preferably 30V or less. The drive frequency is preferably 2 kHz or more, more preferably 5 kHz or more, and is preferably 60 kHz or less, more preferably 50 kHz or less. The amount of ink ejected per droplet is preferably 1.0 pL or more, more preferably 1.5 pL or more, and is preferably 20 pL or less, more preferably 15 pL or less. The print head resolution is preferably 400 dpi (dots per inch) or greater, more preferably 500 dpi or greater.
[0055] The amount of the water-based white ink applied to the fabric is preferably 0.5 g / m2 in terms of dry weight (solid content) from the viewpoint of improving the abrasion fastness and the like. 2 More preferably, 1.0 g / m 2 and preferably 10 g / m 2 Less than 7g / m 2 The following is the result. The printed fabric can be heat-treated as necessary, for example by heat pressing, hot air drying, normal pressure to high pressure steam, or thermofix using infrared rays (lamp). From the viewpoint of efficiently fixing and curing the white ink, the temperature during the heat treatment is preferably 120° C. or higher, and more preferably 130° C. or higher, and is preferably 200° C. or lower, and more preferably 180° C. or lower, and the heat treatment is preferably performed for 30 seconds to 30 minutes. After the heat treatment, the printed material can be washed with water and dried. At this time, if necessary, a soaping treatment may be performed to wash off unfixed titanium oxide with a hot soapy solution or the like. In this manner, a printed textile having an image formed on a fabric by the ink set of the present invention can be obtained. The printed textile thus obtained has excellent friction fastness while maintaining texture, low tackiness, and whiteness comparable to those of textiles obtained by conventional screen printing. EXAMPLES
[0056] In the following Production Examples, Preparation Examples, Examples and Comparative Examples, "parts" and "%" are "parts by mass" and "% by mass" unless otherwise specified. The methods for measuring each physical property are as follows.
[0057] (1) Measurement of polymer weight average molecular weight (Mw) The measurement was performed by gel permeation chromatography (GPC apparatus (HLC-8320GPC) manufactured by Tosoh Corporation, columns (TSKgel SuperAWM-H, TSKgel SuperAW3000, TSKgel guardcolum Super AW-H) manufactured by Tosoh Corporation, flow rate: 0.5mL / min) using a solution of phosphoric acid and lithium bromide dissolved in N,N-dimethylformamide to a concentration of 60mmol / L and 50mmol / L, respectively, as an eluent, and using a monodisperse polystyrene kit with known molecular weight (PStQuick B (F-550, F-80, F-10, F-1, A-1000), PStQuick C (F-288, F-40, F-4, A-5000, A-500), manufactured by Tosoh Corporation) as a standard substance. The measurement sample was prepared by mixing 0.1 g of polymer with 10 mL of the eluent in a glass vial, stirring with a magnetic stirrer at 25° C. for 10 hours, and filtering with a syringe filter (DISMIC-13HP, PTFE, 0.2 μm, Advantec Co., Ltd.).
[0058] (2) Measurement of the average particle size of pigment-containing polymer particles in a pigment water dispersion Cumulant analysis was performed using a laser particle analysis system "ELS-8000" (manufactured by Otsuka Electronics Co., Ltd.) to measure the average particle size. -3 A dispersion liquid diluted with water to a weight percent (solid content conversion) was used. The measurement conditions were a temperature of 25°C, an angle between the incident light and the detector of 90°, and 100 cumulative measurements. The refractive index of water (1.333) was input as the refractive index of the dispersion solvent, and the obtained cumulant average particle size was taken as the average particle size of the pigment-containing polymer particles.
[0059] (3) Measurement of solids concentration of pigment water dispersion 10.0 g of sodium sulfate, which had been kept constant in a desiccator, was weighed out into a 30 mL polypropylene container (φ: 40 mm, height: 30 mm), and about 1.0 g of the sample was added thereto and mixed, then accurately weighed, and maintained at 105°C and a gauge pressure of -0.08 MPa for 2 hours to remove volatile matter, and then left in the desiccator at room temperature (25°C) for another 15 minutes, after which the mass was measured. The mass of the sample after removing the volatile matter was taken as the solid content, and divided by the mass of the sample added to obtain the solid content concentration.
[0060] (4) Measurement of the average primary particle size of titanium oxide The average primary particle diameter of titanium oxide was determined by extracting 500 primary particles of titanium oxide by image analysis using a transmission electron microscope "JEM-2100" (manufactured by JEOL Ltd.), measuring their particle diameters, and calculating the average to obtain the number average particle diameter. Note that when titanium oxide has a major axis and a minor axis, the major axis was used for the calculation.
[0061] (5) Measurement of pH of pigment water dispersion and water-based ink The pH of the water-based ink at 25° C. was measured using a tabletop pH meter “F-71” (manufactured by Horiba, Ltd.) using a pH electrode “6337-10D” (manufactured by Horiba, Ltd.).
[0062] Production Example 1 (Production of White Pigment Water Dispersion) In a 2L plastic container, 6g of polyacrylic acid (PAA, Fujifilm Wako Pure Chemical Industries, Ltd., Mw: 5000), 4.2g of 5N sodium hydroxide aqueous solution, and 4.8g of ion-exchanged water were mixed and dissolved (polymer neutralization degree: 50 mol%) as a polymer dispersant, 300g of titanium oxide (Ishihara Sangyo Kaisha, Ltd., CI Pigment White 6, product name: Typeque CR-80, rutile type, Al·Si treatment, average primary particle diameter of titanium oxide 250 nm) and 255g of water were added, 1000g of zirconia beads were added, and the mixture was dispersed for 8 hours using a tabletop pot mill stand (As One Corporation). The zirconia beads were removed using a metal mesh, and the solid concentration was adjusted with ion-exchanged water to obtain a white pigment aqueous dispersion containing white pigment-containing polymer particles with an average particle diameter of 328 nm (solid concentration: 53.2%, pigment: 52.1%, PAA: 1.1%, pH: 7.3).
[0063] Preparation Examples I-1 to I-8 (Preparation of Water-Based White Inks 1 to 8) The white pigment aqueous dispersion obtained in Production Example 1 was placed in a glass container, and then a carbonate-based urethane resin aqueous emulsion (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Superflex 470) and ion-exchanged water were added, and the mixture was stirred with a magnetic stirrer for 10 minutes to obtain a mixture. While stirring the obtained mixture, a water-soluble organic solvent having the composition shown in Table 1, an acetylene glycol surfactant (manufactured by Nissin Chemical Industry Co., Ltd., trade name: Surfynol 465, an ethylene oxide (10 moles) adduct of 4,7,9-tetramethyl-5-decyne-4,7-diol, active content 100%), and a silicone surfactant (manufactured by Nissin Chemical Industry Co., Ltd., trade name: Silface SAG005, polyether-modified polydimethylsiloxane) were added and stirred for 1 hour. Thereafter, the mixture was filtered using a 5 μm membrane filter (manufactured by Sartorius, trade name: Minisart Syringe Filter) to obtain water-based white inks 1 to 8 shown in Table 1 (solid content concentration: 23.2%, titanium oxide: 12.0%, polymer: 11.2% (PAA: 0.2%, urethane resin: 11.0%), pH: 8.0). The amounts of the white pigment water dispersion and resin emulsion in Table 1 are solid contents.
[0064] [Table 1]
[0065] Preparation Examples II-1 to II-8 (Preparation of Pretreatment Agents 1 to 8) Calcium chloride (manufactured by FUJIFILM Wako Pharmaceutical Co., Ltd.) as a polyvalent metal salt and ion-exchanged water were placed in a glass container and stirred with a magnetic stirrer for 10 minutes to obtain a mixture. While stirring the resulting mixture, an ethylene-vinyl acetate resin emulsion or a styrene-acrylic resin emulsion shown in Table 2 was added so as to obtain the composition shown in Table 2, and the mixture was stirred with a magnetic stirrer for 10 minutes to obtain pretreatment agents 1 to 8. In addition, the "Sumikaflex" shown in Table 2 is manufactured by Sumika Chemtex Corporation, and "LDM7651" is manufactured by Celanese, and the amounts are solid content amounts.
[0066] [Table 2]
[0067] Examples 1 to 13, Comparative Examples 1 to 2 Using an ink set containing a combination of the water-based white inks 1 to 8 obtained in Preparation Examples I-1 to I-8 and the pretreatment agents 1 to 8 obtained in Preparation Examples II-1 to II-8, printed materials were produced by the method shown in (1) below, and the rub fastness, texture, low tackiness, and whiteness were evaluated by the methods shown in (2) to (5) below. The results are shown in Table 3.
[0068] (1) Creation of printed materials The pretreatment agent was uniformly sprayed onto a piece of fabric (Toms Corporation's Printstar Heavy Weight, 100% cotton, black T-shirt cut to A4 size) at an application rate of 10 g per A4 size. After spray application, the fabric was heated and dried for 10 minutes in a constant temperature dryer at 160°C, and then the water-based white ink was filled into the white circulation head of a textile printer (Mastermind Corporation's MMP8130, using color / white ink) in an environment of room temperature 23±1°C and relative humidity 50±5%. A solid image was printed with a duty of 100% under the printing mode (black background / white ink base, printing speed 10 (1440 x 1800 dpi), unidirectional printing) to produce a printed fabric. The obtained printed fabric was immediately dried by heating for 10 minutes in a constant temperature dryer at 160°C.
[0069] (2) Evaluation of friction durability Using a Type II (Gakushin type) friction fastness tester (Daiei Scientific Instruments Manufacturing Co., Ltd., RT-300), the sample was rubbed back and forth 100 times at a speed of 30 reciprocations / min with a load of 200 g over a length of 100 mm. The test piece was 220 mm x 30 mm, and the attached cloth was a black woven fabric (NASKA fabric color broadcloth black) cut to 50 mm x 50 mm and attached to the friction element. L of the attached cloth before and after the friction test * was measured using a spectrophotometer (SpectroEye, manufactured by X-Rite), and the rate of change ΔL * The rub fastness was evaluated from the following. ΔL * = (L of attached fabric before friction test) * / L of attached fabric after friction test * ) x 100 ΔL* The closer to 100%, the better the resistance to friction. If it is 90% or more, there is no problem in practical use.
[0070] (3) Evaluation of texture The resulting printed fabric was pinched at two points with the index finger and thumb of each hand, and moved up and down, front and back, and left and right in opposite directions with both hands, and the texture of the fabric was evaluated according to the following evaluation criteria. If the rating is B or above, the texture is acceptable for practical use. [Evaluation Criteria] A: There is no change in the softness of the fabric before and after printing. B: The fabric becomes slightly stiffer before and after printing. C: The fabric becomes very stiff before and after printing.
[0071] (4) Evaluation of low tack The printed surface of the obtained printed material was touched with the index finger of the dominant hand, and the low tackiness was evaluated based on the stickiness at that time according to the following evaluation criteria. If the evaluation is B or higher, the low tackiness is not a problem for practical use. [Evaluation Criteria] A: It is not sticky at all. B: There is a slight stickiness. C: Very sticky.
[0072] (5) Evaluation of whiteness The lightness of the resulting print L * was measured using a spectrophotometer (SpectroEye, manufactured by X-Rite) to evaluate the whiteness. L * If the whiteness is 90 or more, there is no problem in practical use.
[0073] [Table 3]
[0074] From Table 3, it can be seen that the printed textile obtained using the ink set of the Example has significantly improved friction fastness while maintaining good texture, low tackiness, and whiteness, compared to the printed textile obtained using the ink set of the Comparative Example.
Claims
1. A printing ink set comprising a water-based white ink and a printing pretreatment agent, The pretreatment agent for textile printing contains an ethylene-vinyl acetate resin and water, The water-based white ink contains titanium oxide and one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether and dipropylene glycol monobutyl ether. Ink set for textile printing.
2. 2. The textile printing ink set according to claim 1, wherein the pretreatment agent has an ethylene-vinyl acetate resin content of 0.5% by mass or more and 10% by mass or less.
3. 3. The textile printing ink set according to claim 1, wherein the ethylene-vinyl acetate resin has a glass transition temperature (Tg) of -35°C or higher and 10°C or lower.
4. 4. The textile printing ink set according to claim 1, wherein a total content of the one or more water-soluble organic solvents selected from tripropylene glycol monomethyl ether and dipropylene glycol monobutyl ether is 0.5% by mass or more and 15% by mass or less in the water-based white ink.
5. The textile printing ink set according to any one of claims 1 to 4, wherein the water-soluble organic solvent further contains one or more selected from the group consisting of glycerin and propylene glycol.
6. 6. The textile printing ink set according to claim 1, wherein the titanium oxide is in the form of polymer particles containing titanium oxide.
7. The textile printing ink set according to any one of claims 1 to 6, wherein the textile printing pretreatment agent contains a polyvalent metal salt.
8. The textile printing ink set according to any one of claims 1 to 7, which is for ink-jet textile printing.
Citation Information
Patent Citations
Preprocessing liquid for textile printing, ink set for ink jet textile printing and ink jet textile printing method
JP2013220643A
White fine particle
JP2018090797A
White inkjet ink composition for printing
JP2019035057A
White ink, ink set, method of manufacturing printed matter, and liquid discharge device
JP2019065246A
Recording method and white ink composition
JP2019147339A